Drug design and in-silico study of sulphadiazine schiff base analogues for their potential claim as anti-my cobacterial ligand - T. PRABHA,; T. SIVAKUMAR, (International Journal of Pharma and Bio Sciences, 2018)
The present study was focused to design the series of building blocks with sulphadiazine moiety as a target candidate for antimycobacterial activity. The hypothetically developed sulphadiazine targets are ensured of their reliability on in silico drug designing model. The designed molecules were subjected to a preliminary study of physicochemical properties by screening their violation to Lipinski rule of five if any, predicted for their ADMET profile study by using bioinformatics software viz. Molinspiration, admetSAR search engine. The results obtained from these tools shows there is no Lipinski rule violation, and no toxicity is predicted for this designed molecule. Thus, designed sulphadiazine Schiff base derivatives might serve as the best drug lead for the existence of menacing pathogen Mycobacterium tuberculosis.